Affective and emotional aspects of human-computer interaction : game-based and innovative learning approaches - Pivec, Maja (Future of learning, 2006)
The learning process can be seen as an emotional and personal experience that is addictive and motivates learners to proactive behavior. Divided in three parts, this title discusses major topics such as: emotions, motivation, games, and game-experience.